The electrochemical reduction of aqueous hexamminecobalt(III): Studies of adsorption behaviour with fast scan voltammetry - Ji, X; Chevallier, F; Clegg, A; Buzzeo, M; Compton, R (2005)
The electrochemical reduction of aqueous hexamminecobalt(III) is studied using cyclic voltammetry, observing the current-voltage response using a range of scan rates covering seven orders of magnitude. At lower scan rates, it is clear that the voltammetry is diffusion-controlled, but as the scan rate is increased, the system undergoes a transition to a regime that is governed by adsorption. These experimental results are compared with a previously developed theoretical treatment of adsorption (F.G. Chevallier, O.V. Klymenko, L. Jiang, T.G. Jones, R.G. Compton, J. Electroanal. Chem. 574 (2004) 217). © 2005 Elsevier B.V. All rights reserved.